Multilingualism and museums: Voices of the First World War in the Kobarid Museum (Slovenia) and the Historial de la Grande Guerre (France) - Deganutti, Marianna; Parish, Nina; Rowley, Eleanor (The Journal of Specialised Translation, 2018)
This article focuses on two case studies of First World War museums and examines their museological representation of often difficult multilingual histories and experiences: the Kobarid Museum (Slovenia) and the Historial de la Grande Guerre (France). The Kobarid Museum uses four languages - Slovenian, Italian, German and English - to recall the dramatic events that took place in that borderland during the First World War. The Historial, located in Péronne in the Somme, uses three languages – German, French, and English - to tell the story of that same war from multiple viewpoints both at home and on the front. In both museums, multilingualism plays a vital role in representing complex, interweaving memories in relation to borderlands and the international nature of the First World War, affecting the visitor in a variety of ways. Are the museums using their multilingual approach effectively to promote their messages of peace? Or are they further deepening divides between language-speaking communities and thereby perpetuating animosity? Reflecting on these questions and the use of languages, including processes of translation, within museums more generally advances consideration of the relationship between language, power and the mediation of memory of traumatic events.